Response interference in touch, vision, and crossmodally: Beyond the spatial dimension - Mast, F; Frings, C; Spence, C (2014)
To date, tactile distractor processing has primarily been investigated by focusing on the spatial characteristics of distractors and the impact of their presentation on the orienting of attention. In two experiments, we examined the influence of tactile distractors when the location of stimulus presentation was kept constant, thus controlling for the effects of spatial attention. A response priming paradigm was used in which two stimuli were sequentially presented from the same (fixated) direction. Typically, target responses are facilitated when the previously presented distractor (i.e., the prime) happens to map on to the same response as compared to the distractor maps on to the opposite response. Similar response priming effects were observed for tactile and visual distractors within a unimodal experimental setting (Experiments 1a and 1b). Interestingly, however, when the targets and distractors were presented in different sensory modalities, only the visual distractors exerted a crossmodal effect on the subsequent processing of vibrotactile targets (Experiment 2). These results therefore indicate that visual stimuli automatically trigger their corresponding response even when the task at hand is not visual, whereas tactile stimuli are only processed up to the level of response generation when the participants' task is tactile. © 2014 Springer-Verlag.